The Effect of Transformational and Transactional Leadership on Readiness for Change in the Educational Ministries in Yemen: Learning Organizational Culture as a Mediator - Ali Nasser Ali Al Tahitah (Universiti Sains Islam Malaysia, 2024)
This study examines the impact of leadership style (transformational and transactional) on readiness for change and learning organisational culture, and the effect of learning organisational culture on readiness for change. It also explores the role of learning organisational culture as a mediator in the relationship between “transformational and transactional leadership” and readiness for change. A total of 330 administrative staff of three educational ministries in Yemen, namely (i) Ministry of Higher Education and Scientific Research, (ii) Ministry of Education, and (iii) Ministry of Teachnical Education and Vocational Training participated in this study who were sampled using stratified random sampling approach.The Partial Least Squares (PLS-SEM) software approach was utilised to analyse the data and test the research hypotheses. The findings of this study revealed that all hypotheses were supported but one was not supported. In details,results of the study indicated that transformational leadership has an effect on readiness for change and learning organisational culture. Meanwhile, transactional leadership has an effect on learning organisational culture but has no effect on readiness for change. Moreover, learning organisational culture was found to be a “partial mediator” in the relationship between transformational leadership and readiness for change, and a “fully mediator” in the relations between transactional leadership and readiness for change. In short, the findings show significant implications in terms of the importance of leadership and learning culture towards the readiness for change in the Yemeni educational organisations. Therefore, the current study recommends adopting new strategies to increase the readiness for change among employees in the educational ministries to make the organisations and staff more adaptable with the pace of global changes.